The effect of representative bird model and its impact direction on crashworthiness of aircraft windshield and canopy structure. (November 2019) - Dar, Uzair A; Awais, Muhammad; Mian, Haris H; Sheikh, Muhammad Z
A physically representative bird modeling approach is presented to highlight its significance over traditional substitute bird modeling. To give better representation of a real bird, in this study, the bird was modeled as a fluid body while impacting the rigid and deformable structures. For this, an elastic plastic hydrodynamic material model in conjunction with polynomial equation of state is utilized to model the bird behavior. In addition, smoothed particle hydrodynamics (SPH)-based meshless technique was implemented to build real bird model instead of using finite element-based classical mesh technique in order to avoid mesh connectivity and tangling problems. The numerical scheme was validated by comparing the deformation and pressure profile of the impact on rigid and deformable targets with the available experimental data. The results showed that the physically representative bird impacting the rigid and deformable target give correct values of pressure peak than that of substitute bird. The study also revealed that, the bird impacting the target from bottom direction resulted higher magnitude of pressure shock than head, tail or wing direction. In addition, the instantaneous peak impulse during bottom side impact is more detrimental to impacting structure than other impact directions. Finally, after quantifying the effect of bird impact directions, the work was further extended to establish a full-scale numerical model of a military aircraft windshield–canopy structure to determine its dynamic response against similar impact scenarios. The results showed that the bird impacting from bottom side requires relatively less velocity to initiate failure in the windshield than other impact directions. Thus, the bird impacting from its bottom side was recognized as the most dangerous impact condition for structural integrity of windshield.